Evaluasi Program Sekolah Rohani Islam dalam Pembinaan Akhlak di SMA Plus Negeri 17 Palembang - M Nur Wahyudi; Zainal Berlian; Muh Misdar (Program Magister Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2020)
This study aims to determine the planning, implementation and evaluation of school programs in Islamic spirituality at SMA plus Negeri 17 Palembang. This research is motivated by school programs related to Islamic Education in implementing the results of the school program, because the school program hopes to shape Islamic character / character. So the success of a school, especially high school plus 17 Palembang state is determined by the success of the program. Research methods: this study uses qualitative methods that contain: (1) Research patterns / types (2) Research locations (3) Researchers presence (4) Data collection procedures (5) Data analysis techniques (6) Checking the validity of the data. The type of research used is a case study, which is one of the strategies and methods of qualitative data analysis that emphasizes specific cases that occur on the object of analysis. Research results: evaluation of school programs in the Islamic spirit in this research can be done through planning, implementing and evaluating. School program planning is determined by the school through a number of work procedures for school principals and vice-principals of the students who compile development programs, such as: 5S (smiles, greetings, greetings, courtesy and courtesy), BTA (Read Al Qur'an) and Islamic Art. The implementation of the school program process by taking into account its steps through its work programs and evaluations by verifying the existence of moral values instilled in school program activities. 5S moral values are not indivisualism, polite, BTA moral values is to be fluent in reading the Qur'an, hafidz and hafidzoh; and the moral values that are implanted can produce the soul of Islamic art.